2016
DOI: 10.1117/1.jbo.21.3.035003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and standardization of tissue-simulating protoporphyrin IX optical phantoms

Abstract: Abstract. Optical devices for measuring protoporphryin IX (PpIX) fluorescence in tissue are routinely validated by measurements in optical phantoms. Yet there exists limited data to form a consensus on the recipe for phantoms that both mimic the optical properties found in tissue and yield a reliable and stable relationship between PpIX concentration and the fluorescence remission intensity. This study characterizes the influence of multiple phantom components on PpIX fluorescence emission intensity, using Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…1 by addition of HCl into S 0 to reach a pH of 5 and then addition of 1 mL of Tween 20 and 1 mL of Intralipid, as proposed in Ref. 15. This fit yields the two parameters α 634 and α 620 .…”
Section: Data Processingmentioning
confidence: 96%
See 2 more Smart Citations
“…1 by addition of HCl into S 0 to reach a pH of 5 and then addition of 1 mL of Tween 20 and 1 mL of Intralipid, as proposed in Ref. 15. This fit yields the two parameters α 634 and α 620 .…”
Section: Data Processingmentioning
confidence: 96%
“…PpIX concentration was set around 10 −5 mol∕L to be close to in vivo concentrations. 7,13 Additional components were sequentially added as proposed by Marois et al 15 to get various microenvironments of PpIX. Solutions were prepared by dissolving 6.1 mg of PpIX (Sigma Aldrich, Saint Louis) into 10 mL of DMSO to get a stock solution at 1.2 × 10 −3 mol∕L.…”
Section: Optical Phantom Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…[37]. We u by [44] cleaved so that excited tissue area and emitting tissue area are the same. Light goes through a low pass filter with a rejection band between 450 nm and 700 nm.…”
Section: Spectrosmentioning
confidence: 99%
“…22,23 The objective of this study was to develop a model producing endogenous levels of PpIX comparable to those observed in the abovementioned clinical applications. Such a model is of high interest to optimize or study basic mechanisms involved in PDT and PDD, such as the influence of agents or environmental factors on the modulation of the PpIX biosynthetic pathway; 23,24 the study of steady-state and time-resolved spectroscopy of PpIX produced endogenously, in particular, its dependence on environmental factors [temperature and oxygen partial pressure (pO 2 )]; 12,13,25 the development of optical phantoms mimicking the PpIX fluorescence spectroscopy and intensity observed in tumors, 26,27 the study of agents modulating the production of ROS, including singlet oxygen, to optimize and/or monitor PDT. 28 Thus, the determination of the conditions reproducibly leading to the maximal PpIX fluorescence intensity produced by Saccharomyces cerevisiae was studied and is reported in this paper.…”
Section: Introductionmentioning
confidence: 99%